Biological and Molecular Docking Evaluation of a Benzylisothiocyanate Semisynthetic Derivative From Moringa oleifera in a Pre-clinical Study of Temporomandibular Joint Pain - Silveira, Felipe Dantas; Gomes, Francisco Isaac Fernandes; do Val, Danielle Rocha; Freitas, Hermany Capistrano; de Assis, Ellen Lima; de Almeida, Diana Kelly Castro; Braz, Helyson Lucas Bezerra; Barbosa, Francisco Geraldo; Mafezoli, Jair; da Silva, Marcos Reinaldo; Jorge, Roberta Jeane Bezerra; Clemente-Napimoga, Juliana Trindade; et al. (Frontiers in Neuroscience, 2022)
Objective: Moringa oleifera possesses multiple biological effects and the 4-[(4’-O-acetyl-α-L- rhamnosyloxy) benzyl] isothiocyanate accounts for them. Based on the original isothiocyanate molecule we obtained a semisynthetic derivative, named 4-[(2’,3’,4’-O-triacetyl-α-L-rhamnosyloxy) N-benzyl] hydrazine carbothioamide (MC-H) which was safe and effective in a temporomandibular joint (TMJ) inflammatory hypernociception in rats. Therefore, considering that there is still a gap in the knowledge concerning the mechanisms of action through which the MC-H effects are mediated, this study aimed to investigate the involvement of the adhesion molecules (ICAM-1, CD-55), the pathways heme oxygenase-1 (HO-1) and NO/cGMP/PKG/K+ATPATP, and the central opioid receptors in the efficacy of the MC-H in a pre-clinical study of TMJ pain. Methods: Molecular docking studies were performed to test the binding performance of MC-H against the ten targets of interest (ICAM-1, CD55, HO-1, iNOS, soluble cGMP, cGMP-dependent protein kinase (PKG), K+ATPATP channel, mu (µ), kappa (k), and delta (δ) opioid receptors). In in vivo studies, male Wistar rats were treated with MC-H 1 µg/kg before TMJ formalin injection and nociception was evaluated. Periarticular tissues were removed to assess ICAM-1 and CD55 protein levelsexpression by Western blotting. To investigate the role of HO-1 and NO/cGMP/PKG/K+ATP pathways, the inhibitors ZnPP-IX, aminoguanidine, ODQ, KT5823, and or glibenclamide were used. To study the involvement of opioid receptors, rats were pre-treated (15 min) with an intrathecal injection of non-selective inhibitor naloxone or with CTOP, naltrindole, and or norbinaltorphimine. Results: All interactions presented acceptable binding energy values (below -6.0 kcal/mol) which suggest MC-H might strongly bind to its molecular targets. MC-H reduced the protein levelsexpression of ICAM-1 and CD55 in periarticular tissues. ZnPP-IX, naloxone, CTOP, and naltrindole reversed the antinociceptive effect of MC-H. Conclusion: MC-H demonstrated antinociceptive and anti-inflammatory effects peripherally by the activation of the HO-1 pathway, as well as through inhibition of the protein levels of adhesion molecules expression, and centrally by μ and δ opioid receptors.